Nanostructured magnetic nanocomposites as MRI contrast agents. Issue 11 (23rd February 2015) - Peng, Erwin; Wang, Fenghe; Xue, Jun Min
Abstract : The development of water-soluble nanostructured magnetic nanocomposites based on hydrophobic magnetic nanoparticle assemblies using an organic functional coating for MRI contrast agent applications was discussed. Abstract : Magnetic resonance imaging (MRI) has become an integral part of modern clinical imaging due to its non-invasiveness and versatility in providing tissue and organ images with high spatial resolution. With the current MRI advancement, MRI imaging probes with suitable biocompatibility, good colloidal stability, enhanced relaxometric properties and advanced functionalities are highly demanded. As such, MRI contrast agents (CAs) have been an extensive research and development area. In the recent years, different inorganic-based nanoprobes comprising inorganic magnetic nanoparticles (MNPs) with an organic functional coating have been engineered to obtain a suitable contrast enhancement effect. For biomedical applications, the organic functional coating is critical to improve colloidal stability and biocompatibility. Simultaneously, it also provides a building block for generating a higher dimensional secondary structure. In this review, the combinatorial design approach by a self-assembling pre-formed hydrophobic inorganic MNPs core (from non-polar thermolysis synthesis) into various functional organic coatings ( e.g. ligands, amphiphilic polymers and graphene oxide) to form water soluble nanocomposites will be discussed. The resultant magnetic ensembles were classified based on their dimensionality, namely, 0-D, 1-D, 2-D and 3-D structures. This classification provides further insight into their subsequent potential use as MRI CAs. Special attention will be dedicated towards the correlation between the spatial distribution and the associated MRI applications, which include (i) coating optimization-induced MR relaxivity enhancement, (ii) aggregation-induced MR relaxivity enhancement, (iii) off-resonance saturation imaging (ORS), (iv) magnetically-induced off-resonance imaging (ORI), (v) dual-modalities MR imaging and (vi) multifunctional nanoprobes.